2015
DOI: 10.1016/j.nicl.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting brain patterns of writing-related DTI parameters, fMRI connectivity, and DTI–fMRI connectivity correlations in children with and without dysgraphia or dyslexia

Abstract: Based on comprehensive testing and educational history, children in grades 4–9 (on average 12 years) were diagnosed with dysgraphia (persisting handwriting impairment) or dyslexia (persisting word spelling/reading impairment) or as typical writers and readers (controls). The dysgraphia group (n = 14) and dyslexia group (n = 17) were each compared to the control group (n = 9) and to each other in separate analyses. Four brain region seed points (left occipital temporal gyrus, supramarginal gyrus, precuneus, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 41 publications
6
67
3
1
Order By: Relevance
“…Finally, this research supplements prior research showing that typically developing readers and writers differ in structural and functional connectivity on handwriting and spelling tasks and planning for text-level composing [53]. Only those with dyslexia with and without dysgraphia or with dysgraphia were included in the current study, which showed response to instruction in that correlations between brain connectivity and proportion of ideas units in notes and summaries increased after specialized instruction.…”
Section: Discussionsupporting
confidence: 70%
“…Finally, this research supplements prior research showing that typically developing readers and writers differ in structural and functional connectivity on handwriting and spelling tasks and planning for text-level composing [53]. Only those with dyslexia with and without dysgraphia or with dysgraphia were included in the current study, which showed response to instruction in that correlations between brain connectivity and proportion of ideas units in notes and summaries increased after specialized instruction.…”
Section: Discussionsupporting
confidence: 70%
“…Impairment was defined as below −2/3 SD on relevant measures. For brain evidence that control SLD groups differ from each other and from controls, see Richards et al (in press) and Berninger et al (2015).…”
Section: Methodsmentioning
confidence: 99%
“…The amount of connectivity detected with other brain regions from a given seed, even after controlling for multiple comparisons [7], may be surprising to some. The brain atlas often used in connectome research [8-11] and also used in this fMRI connectivity study—the Jülich histological (cyto-and myeloarchitectonic) atlas [12,13] provides much more fine-grained detail and increases the number of potential connections compared to prior atlases with fewer locations within regions.…”
Section: Introductionmentioning
confidence: 99%